Social Entrepreneurship and Social Venture in Nepal, Case of Martyrs Memorial Park (Sahid Smarak), Hetauda, Nepal - Silwal, Yam Bahadur (International Research Journal of MMC, 2020)
This study primarily tried to find out social entrepreneurship practices in Nepal, though this is an young phenomena for scholarly in Nepal. Study followed exploratory case type and selected Martyrs Memorial Park (Sahid Smarak) as a case so that it is a qualitative research. Social entrepreneurship is phenomena about utilization of creative idea of individuals for the society and social benefits through entrepreneurship and entrepreneurial venture creation. Martyrs Memorial Park (Sahid Smarak) is a social venture situated in Hetauda, Bagmati province, Nepal established by social and political personalities. This venture is found as a good practice of social entrepreneurship that generate revenue for the society, providing employment opportunities, utilizing resources, paying tax, contributing to uplift tourism, giving recognition of the area and members of the executive committee and council members as well. This venture became a model for others and many are trying to implement this in another part of the country. Social entrepreneurship process model found which started from social or political person with entrepreneurship intention that converted into entrepreneurial behavior and realize the social venture. Then economic outputs bring transformation in the society and generate social entrepreneurs' personality enrichment